Facile in situ synthesis of silver nanoparticles on tannic acid/zein electrospun membranes and their antibacterial, catalytic and antioxidant activities. (15th November 2020) - Zhan, Fuchao; Yan, Xiangxing; Sheng, Feng; Li, Bin
Highlights: The morphology of the membranes was significantly depending on the concentration of Tan. A novel material containing AgNPs was prepared by electrospinning and one-step reduction method. Electrospun membrane with AgNPs/TA/Zein has antimicrobial activity against E. coli and S. aureus . The AgNPs/TA/Zein electrospun membrane has tremendous application potential. Abstract: This study demonstrates the development of biocompatible Ag nanoparticles/Tannic acid/Zein electrospun membranes with synergistic antibacterial, catalytic and antioxidant activity. The optimal spinning concentration of zein was 32 wt%. The prepared zein electrospun membranes were immersed into tannic acid (TA) solution to investigate the effects of TA concentrations, pH, temperature and time on the loading amount of TA. Then, the TA/Zein electrospun membranes were immersed into a silver nitrate solution to reduce the AgNPs in situ. The morphology of the electrospun membranes was characterized by scanning electron microscopy (SEM). UV–visible spectrophotometer, Fourier-transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD) were used to carry out the loading amount of TA and Ag nanoparticles (AgNPs). Finally, the antioxidant, antibacterial and catalytic activity of TA/Zein and AgNPs/TA/Zein electrospun membranes were studied. It was found that the AgNPs/TA/Zein electrospun membranes with different TA concentrations have certain antibacterial, antioxidation and catalytic ability, which may be of interest for the development of active packaging that could extend the shelf life of perishable foods.